Geografia e saúde : análise espacial da ocorrência da esquistossomose na área de rizicultura do município de Ilha das Flores-SE/BR - Silva, Marília Matos Bezerra Lemos (2012)
Schistosomiasis is a millennial disease and constitutes a public health problem worldwide. According to the World Health Organization - WHO (2009), there is 235 million cases of schistosomiasis, with 732 million people at risk of infection in areas worldwide. In Brazil, the disease is found mainly in the Northeast and the state of Minas Gerais. According to the Health s Ministry - MS (2009), the state of Sergipe has the highest prevalence and incidence of disease in the Federation. Being identified areas of high endemicity, such as the city of Ilha das Flores, the subject of this research, which showed about 46.5% of the infected population analyzed in 2007. It is known that the study area is highlighted as a major producer of rice in the Northeast. This activity has a significant economic and strategic value to the city. However, the areas of extenseis type irrigation are recognized worldwide as major sources of transmission of schistosomiasis, because they have conditions conducive to the creation of shellfish and dissemination of S. mansoni infection. Based on this hypothesis, the objective of this study is to analyze the spatial dynamics of the factors that make the city studied endemic for this infection. In order to achieve the proposed objective, initially was to the prevalence of the disease in the municipality through an epidemiological survey of 500 residents between 2009 and 2010. Then, from the diagnosis of environmental conditions, socioeconomic and cultural, through field work, geostatistical and spatial analysis, and preparation of thematic maps, and map the vulnerability to the disease. Of the 500 individuals who participated in this study, 120 were positive for schistosomiasis, which corresponds to 24% of the sampling universe (BCA (Bootstrap) 95% [20.4 to 27.6]). From the positive individuals, the multinomial model of spatial analysis, Kernel density estimator, specialized areas more vulnerable to disease occurrence, and punctuated areas in which quality of life is precarious. By combining the results of geology, pedology and geomorphology and the characterize land use, it was noted that the incidence of the disease occurred in the area of the plain fluviolagunar, predominantly agricultural areas, where urban areas are located in the city. Thus it was possible to associate the occurrence of disease in the city to work in irrigated farming, and the existence of favorable ecological characteristics of the proliferation of snails (intermediate hosts of S. mansoni). The geostatistical analyzes ratified the information cited to establish standards that identify populations most susceptible to infection. What associations were identified between S.mansoni and: being male, 65.2% of positive (PR = 2.0, 95% CI 1.27 to 3.26, p = 0.003), have low education level (PR = 7.1, 95% CI 2.41 to 20.93, p <0.001), having low income (family income < U.S 273,00) (PR = 1.8, 95% CI 1.28 to 2.60, p = 0.0005), have any level of contact with natural water sources (PR = 1.9, 95% CI 1.36 to 2.59, p <0.001), time of contact with natural water sources (more than 6 hours per week) ( PR 3.6 95% CI 1.05 to 12.32, p = 0.04), be a farmer (PR = 2.7, 95% CI, 1.29 to 5.40, p <0.001) and / or be a fisherman (PR = 3.3, 95% CI 1.39 to 7.69, p <0.001). It was concluded that the population of the city of Ilha das Flores-SE is highly vulnerable to the occurrence of schistosomiasis and needs the attention of government to reverse this situation, trying to solve the problems, that are associated to schistosomiais transmission of this population.